2019
DOI: 10.1210/clinem/dgz200
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Patients with Nelson’s Syndrome after Primary Treatment: A Multicenter Study from 13 UK Pituitary Centers

Abstract: Context Long-term outcomes of patients with Nelson’s syndrome (NS) have been poorly explored, especially in the modern era. Objective To elucidate tumor control rates, effectiveness of various treatments, and markers of prognostic relevance in patients with NS. Patients, design, and setting Retrospective cohort study of 68 patients from 13 UK pituitary center… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 58 publications
1
40
0
Order By: Relevance
“…there is not general guideline as approach but radiotherapy, neurosurgery of the pituitary gland an and potential use of somatostatin analogues and/or dopamine agonists are the therapy lines (26,27). a study published in 2019 showed that 38% of the subjects with nelson's syndrome displayed some level of progression during a follow-up of 10 years (28). the risk of progression is higher if complex therapies are applied to Cushing's disease but this may also be correlated with a more severe form of disease (28).…”
Section: Nelson's Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…there is not general guideline as approach but radiotherapy, neurosurgery of the pituitary gland an and potential use of somatostatin analogues and/or dopamine agonists are the therapy lines (26,27). a study published in 2019 showed that 38% of the subjects with nelson's syndrome displayed some level of progression during a follow-up of 10 years (28). the risk of progression is higher if complex therapies are applied to Cushing's disease but this may also be correlated with a more severe form of disease (28).…”
Section: Nelson's Syndromementioning
confidence: 99%
“…a study published in 2019 showed that 38% of the subjects with nelson's syndrome displayed some level of progression during a follow-up of 10 years (28). the risk of progression is higher if complex therapies are applied to Cushing's disease but this may also be correlated with a more severe form of disease (28). nelson-Salassa syndrome has been revealed in half of the persons with Cushing's disease treated with bilateral adrenal removal associating a mild evolution (29).…”
Section: Nelson's Syndromementioning
confidence: 99%
“…When feasible, surgical resection of the Nelson’s syndrome tumor is commonly recommended. Reported success rates of pituitary surgery varies widely from 10 to 70% [ 11 , 36 38 ]. Higher rates of remission have been associated with smaller tumors, adjuvant radiotherapy, and absence of tumor invasion into the dura mater [ 11 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Reported success rates of pituitary surgery varies widely from 10 to 70% [ 11 , 36 38 ]. Higher rates of remission have been associated with smaller tumors, adjuvant radiotherapy, and absence of tumor invasion into the dura mater [ 11 , 36 , 37 ]. The most common complications are hypopituitarism, cerebrospinal fluid leak, and meningitis occurring in up to 69%, 15%, and 8% of postoperative patients, respectively [ 38 – 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation